THE PROBLEMS OF SKEPTICISM INTERPRETATION: FROM SEXTUS EMPIRICUS TO D. HUME - Загороднюк, В. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
This article is devoted to the theoretical foundations of the analysis of skepticism. The correctness of the existing distribution of skepticism to "complete" to "incomplete" is denied wth consideration of the philosophical concepts of Sextus Empiricus and David Hume. Also there was made the revision of existing biased views on the problem of skepticism.